HSF-1, HIF-1and HSP90 expression on recombinant Pichia pastoris under fed-batch fermentation - Zepeda, Andrea B. (2014)
Pichia pastoris is a methylotrophic yeast used as an efficient expression system for heterologous protein production as compared to other expression systems. Considering that every cell must respond to environmental changes to survive and differentiate, determination of endogenous protein related to heat stress responses and hypoxia, it would necessary to establish the temperature and methanol concentration conditions for optimal growth. The aim of this study is characterize the culture conditions through the putative biomarkers in different conditions of temperature and methanol concentration. Three yeast cultures were performed: 3X = 3% methanol -10 °C, 4X = 3% methanol -30 °C, and 5X = 1% methanol -10 °C. The expression level of HIF-1α, HSF-1, HSP-70 and HSP-90 biomarkers were measured by Western blot and in situ detection was performed by immunocytochemistry. The western blot results of HIF-1α and HSP-90 did not indicate statistically significant in the culture conditions studied. Respect to biomarkers location, HIF-1α and HSP-90 presented differences between cultures. In conclusion, the results suggest the cultures in a hypoxic condition produce a high density and yeast cells smaller. Beside the high density would not necessary related with a high production of recombinant proteins in modified-genetically P. pastoris.